Growth Promoting Effects of Vermiwash and Panchagavya on Dolichus Lablab under Field Experimental Conditions - Maheswari, V.N.; Srikumaran, M.P.; Rekha, G.S.; Elumalai, D.; Kaleena, P.K. (International Journal of Applied Sciences and Biotechnology, 2017)
The present study explores the growth promoting effects of vermiwash and panchagavya on Dolichus lablab. Vermiwash was obtained from the vermicomposting unit and panchagavya was prepared using cow products such as milk, curd, urine, ghee and dung. Different concentrations of vermiwash and panchagavya (5:2%, 10:3% and 15:4%) were applied to the bean plants once in every week for 90 days. The exo-morphological characters such as shoot length, internode length, diameter of the internode, number of leaves, leaf surface area and chlorophyll content were recorded prior to every treatment in all the groups. Interestingly, 10:3% vermiwash and panchagavya treated lablab beans showed better growth promoting effects than the other plants. Thus, the results of the present study clearly suggest that 10:3% vermiwash and panchagavya could be used as effective foliar spray in the near future. Int J Appl Sci Biotechnol, Vol 4(4): 513-518